Romiplostim dose–response in patients with myelodysplastic syndromes. (20th May 2013) - Perez Ruixo, Juan Jose; Doshi, Sameer; Wang, Yow‐Ming C.; Mould, Diane R.
Abstract : Aim: To characterize the romiplostim dose–response in subjects with low or intermediate‐1 risk myelodysplastic syndromes (MDS) receiving subcutaneous romiplostim. Methods: Data from 44 MDS subjects receiving subcutaneous romiplostim (dose range 300–1500 μg week −1 ) were used to develop a pharmacodynamic model consisting of a romiplostim‐sensitive progenitor cell compartment linked to the peripheral blood compartment through four transit compartments representing the maturation in the bone marrow from megakaryocytes to platelets. A kinetics of drug effect model was used to quantify the stimulatory effect of romiplostim on the proliferation of sensitive progenitor cells and pharmacodynamics‐mediated disposition was modelled by assuming the kinetics of drug effect constant ( kDE ) to be proportional to the change in platelet count relative to baseline. Results: The estimated values (between subject variability) for baseline platelet count, mean transit time, and kDE were 24 × 10 9  l −1 (47%), 9.6 days (44%) and 0.28 days −1, respectively. MDS subjects had a shorter platelet lifespan (42 h) than healthy subjects (257 h). Romiplostim effect was described for responders (78%) and non‐responders (22%). The average weekly stimulatory effect of romiplostim on the production rate of sensitive progenitor cells at baseline was 269% per 100 μg week −1 for responders. Body weight, age, gender and race were not statistically related to romiplostim pharmacodynamic parameters. Visual predictive checks confirmed the model adequacy. Conclusion: The time course of platelet counts in MDS subjects receiving subcutaneous administration of escalating doses of romiplostim was characterized and showed a linear dose–response for romiplostim responders to increase the platelet counts.